Amperometric glucose biosensor based on layer-by-layer films of microperoxidase-11 and liposome-encapsulated glucose oxidase - Graca, J. S.; Oliveira, R. F. de [UNESP]; Moraes, M. L. de; Ferreira, M. (Elsevier B.V., 2014)
An important step in several bioanalytical applications is the immobilization of biomolecules. Accordingly, this procedure must be carefully chosen to preserve their biological structure and fully explore their properties. For this purpose, we combined the versatility of the layer-by-layer (LbL) method for the immobilization of biomolecules with the protective behavior of liposome-encapsulated systems to fabricate a novel amperometric glucose biosensor. To obtain the biosensing unit, an LbL film of the H2O2 catalyst polypeptide microperoxidase-11 (MP-11) was assembled onto an indium-tin oxide (ITO) electrode followed by the deposition of a liposome-encapsulated glucose oxidase (GOx) layer. The biosensor response toward glucose detection showed a sensitivity of 0.91 +/- 0.09 (mu A/cm(2))/mM and a limit of detection (LOD) of 8.6 +/- 1.1 mu M, demonstrating an improved performance compared to similar biosensors with a single phospholipid-liposome or even containing a non-encapsulated GOx layer. Finally, glucose detection was also performed in a zero-lactose milk sample to demonstrate the potential of the biosensor for food analysis. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Glucose biosensor; Microperoxidase-11; Layer-by-layer technique; Liposome; Biosensor